The Impact of Tobacco Control Policies on Health Justice: A Case Study of Indonesia’s Smoking Epidemic (Indonesian Health Justice Review, 2024)
Indonesia has one of the highest rates of tobacco use in the world, which has led to severe public health consequences, particularly for vulnerable populations. This paper investigates the impact of Indonesia’s tobacco control policies on health justice, focusing on the effectiveness of measures aimed at reducing smoking rates and mitigating tobacco-related health disparities. The study uses a combination of policy analysis, statistical data on smoking prevalence, and interviews with public health experts and smokers to assess the outcomes of tobacco control policies. Findings indicate that while some policies, such as smoking bans in public spaces and graphic health warnings on cigarette packages, have had a positive impact, smoking rates remain high due to cultural acceptance, aggressive tobacco industry marketing, and weak enforcement of regulations. The research argues that tobacco control policies in Indonesia need to be strengthened to address the root causes of tobacco use and protect vulnerable groups, including low-income individuals and children. Recommendations include expanding public health education campaigns, increasing tobacco taxes, and enforcing stricter regulations on tobacco advertising. The paper concludes that a more robust and equitable approach to tobacco control is essential for improving health justice in Indonesia.